PENINGKATAN KETERAMPILAN MENULIS TEKS EKSPLANASI MELALUI MEDIA BERITA MENGGUNAKAN METODE STAD (STUDENT TEAM ACHIEVEMENT DIVISION) PADA SISWA KELAS X1 SMKN 1 BINONG - Andri Purwanugraha; Della Fitria Amanda (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
In learning to write at school, especially at SMKN I Binong based on the results of interviews and observations that have been carried out, it shows the low writing ability of students because students pay less attention to cohesion and coherence in paragraphs. This research was obtained from one class, namely class XI which was used as the experimental class. Data were obtained from 9 students to write explanatory texts and the results of interviews with Indonesian language teachers. Furthermore, the data were analyzed using the formula for finding the average score, normality test, homogeneity test, hypothesis testing, and N-Gain test. The results of the students' pretest in learning to write explanatory texts before using the STAD (Student Team Achievement Division) method were still very less than the data on the entire object found. The lowest score is 40, the highest score is 80, and students get an average score of 63.33 for writing explanatory text, the score is said to be very low. Because the Minimum Completeness Criteria (KKM) in schools is 70. The results of the posttest in writing explanatory texts the lowest score is 60, the highest score is 90, and the average posttest in the experimental class is 74.44. The improvement of explanatory text writing skills using the STAD (Student Team Achievement Division) method has been proven by researchers to improve learning to write explanatory texts. The STAD (Student Team Achievement Division) method makes the learning atmosphere in the classroom more active in asking questions, is conducive, collaboration between students, solving problems, and can make it easier for students when retelling an incident so as to produce better explanatory text writing results.